The development of light ion injector for the plasma diagnostic system based on beam emission spectroscopy - Chmyga, A.A.; Deshko, G.N.; Komarov, A.D.; Kozachek, A.S.; Krupnik, L.I.; Khrebtov, S.M.; Tashchev, Yu.I.; Zhezhera, A.I. (Вопросы атомной науки и техники, 2012)
The development of light ion injector and neutralizer for the BES plasma diagnostic system and its first experimental results are presented in this work. This injector will be used for neutral beam plasma diagnostic systems. Diagnostic systems based on neutral beams of Li or Na atoms can be used to study the spatial plasma density profiles, impurity ions and magnetic field distribution in the border region of the plasma fusion devices. This method is based on the detection of the probe beam glow of atoms excited by the plasma electrons. These diagnostic systems consist of two main parts – the neutral beam injector (including the ion beam accelerator and neutralizer) and the secondary light signal registration system. Light ion beam accelerator based on the five-electrode ion-optical system, in contrast to the classical three-electrode system, delivers beams of lithium or sodium with current 3…5 mA at a beam energy 20…25 keV. The neutralizer is based on the supersonic jet of sodium vapor formed by Laval nozzle. The first experiments of neutralizing the ion beam with a transverse supersonic atomic jet was done. Представлена разработка инжектора легких ионов и нейтрализатора для ПЭС-системы диагностики плазмы и первые экспериментальные результаты. Этот инжектор будет использован для диагностики плазмы с помощью пучка нейтральных атомов. Диагностические системы, основанные на нейтральных пучках атомов Li или Na, могут быть использованы для исследования пространственных профилей плотности плазмы, примесей ионов и распределения магнитного поля в пограничных областях плазмы термоядерных установок. Этот метод основан на регистрации свечения атомов зондирующего пучка, возбуждаемых электронами плазмы. Эти диагностические системы состоят из двух основных частей: инжектора нейтральных атомов (включающего ускоритель пучка ионов и нейтрализатор) и системы регистрации излучения. Ускоритель легких ионов, базирующийся на пятиэлектродной ионно-оптической системе, в отличие от классической трехэлектродной, позволяет получать пучки ионов лития или натрия с током 3…5 мА при энергии пучка 20…25 кэВ. Нейтрализатор основан на сверхзвуковой струе паров натрия, формируемой с помощью сопла Лаваля. Проведены первые эксперименты по нейтрализации пучка ионов с помощью поперечной сверхзвуковой струи. Представлена розробка інжектора легких іонів і нейтралізатора для системи ПЕС діагностики плазми та перші експериментальні результати. Цей інжектор буде використаний для діагностики плазми за допомогою пучка нейтральних атомів. Діагностичні системи, засновані на нейтральних пучках атомів Li або Na, можуть бути використані для дослідження просторових профілів густини плазми, домішкових іонів і розподілу магнітного поля в приграничних областях плазми термоядерних установок. Цей метод заснований на реєстрації світіння атомів зондуючого пучка, збуджуваних електронами плазми. Ці діагностичні системи складаються з двох основних частин: інжектора нейтральних атомів (що включає прискорювач пучка іонів і нейтралізатор) та системи реєстрації випромінювання. Прискорювач легких іонів, який базується на п’ятиелектродній іонно-оптичній системі, на відміну від класичної трьохелектродної, дозволяє отримувати пучки іонів літію або натрію зі струмом 3…5 мА при енергії пучка 20…25 кеВ. Нейтралізатор заснований на надзвуковому струмені пари натрію, формованої за допомогою сопла Лаваля. Проведені перші експерименти з нейтралізації пучка іонів за допомогою поперечного надзвукового струменя.